Relationship Between Infant and Child Feeding History (PMBA), Infectious Disease History and Food Intake in Wasting Toddlers - Febranitami, Catur Amalia; Sajiman; Hariati, Niken Widyastuti (Jurnal Riset Pangan dan Gizi, 2025)
Improving human resource quality depends on good nutrition, especially for pregnant women and young children. Wasting remains a challenge in Indonesia, including at Puskesmas Landasan Ulin, with cases rising from 5.39% in 2023 to 9.23% in February 2024. This condition is influenced by imbalanced nutrient intake, improper feeding practices, and infections such as acute respiratory infections (ARI), pneumonia, and diarrhea. This study aims to analyze the relationship between infant and young child feeding (IYCF) history, infectious diseases, and dietary intake in wasted toddlers at Puskesmas Landasan Ulin. This research is an analytical observational study with a case-control design. It was conducted in the working area of Puskesmas Landasan Ulin in November 2024. The sample consisted of 59 children aged 6–59 months with wasting as the case group and 118 children without wasting as the control group. There is a significant relationship between IYCF history (P-value = 0.032), history of infectious diseases (P-value = 0.017, OR = 95% CI 1.303–8.202), and dietary intake (P-value = 0.000, OR = 95% CI 1.955–9.361) with wasting in children. Enhancing mothers' knowledge of IYCF practices by increasing the number of trained health cadres and promoting IYCF through media campaigns is crucial.